Case Series of Two Patients with Primary Malignant Melanoma of the Lacrimal Sac - Tessa H Anindya; Neni Anggraini; Evelina Kodrat (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Background: To demonstrate two rare case of primary malignant melanoma of lacrimal sac. Case Illustration: Patients were both female, 38-year-old and 46-year-old, with lacrimal sac mass,bloody discharge and epiphora. The first patient was previously diagnosed with chronic dacryocystitisand treated with antibiotics and anti-inflammation for two months which resulted in worsen conditionand enlarged swelling. Computed tomography scan revealed solid mass at lacrimal sac 13 x 12 x 7.4millimeters in size with no bone destruction. Patient underwent total mass removal surgery, whichrevealed solid highly pigmented mass. The second patient also had enlarged mass within two months.Other complaints include obstructed left nose and epistaxis. Computed tomography scan revealed solidmass at left medial canthal region involving inferior orbit, nasolacrimal duct, left nose cavity, andmaxillary sinus. Incisional biopsy revealed a malignant melanoma. Patient underwent eye exenteration,maxilectomy, and radical neck dissection. Conclusion: Primary malignant melanoma of the lacrimal sac is a rare case and often mimics chronicdacryocystitis. It’s imporant to understand this disease entity to make accurate diagnosis and managementwith the help of imaging modality.